Effect of Eight Weeks of Modified Pilates Training on Pulmonary Function and Quality of Life of Veterans Exposed to Chemical Warfare - Gh. Ghasemi; P. Barati Rokati; O.R. Salehi (Afarand Scholarly Publishing Institute, 2019)
Aim(s): Injury with chemical agents effects on the physical, mental, social and spiritual dimension of quality of life. The aim of the present study was to investigate the effect of eight weeks of modified Pilates training on pulmonary function and quality of life in veterans exposed to chemical warfare agents. Materials and Methods: This semi-experimental study with pretest-posttest design and a control group was conducted in Izeh County in 2016. The study was carried out on 28 male veterans who were exposed to chemical warfare agents. The subjects were selected by convenience sampling method and randomly assigned into the control group (n=15) and training group (n=13). The training group performed the modified Pilates training for 8 weeks, 3 sessions-in 60 minutes per week. The control group did not participate in any particular training program during this period. Muscular strength, pulmonary index, and quality of life of the subjects before and after the training period were measured by hand dynamometer, spirometer, and quality of life questionnaire respectively. Data were analyzed through SPSS 22 software using paired sample t-test and univariate analysis of covariance test. Findings: The mean scores of forced vital capacity and the quality of life in terms of mental and physical dimensions in the posttest step were significantly higher than the pretest step (p=0.001). By removing the pretest effect, the mean scores of back muscular power (p=0.03), forced vital capacity (p=0.02) and quality of life (p=0.001) in the training group were significantly higher than the control group. Conclusion: Eight weeks of modified Pilates training can be effective in the improvement of pulmonary function and quality of life of veterans exposed to chemical warfare agents.